PENGEMBANGAN E - MODUL BERBASIS APLIKASI FLIPBOOK SUBTEMA PERTUMBUHAN DAN PERKEMBANGAN MANUSIA - Husni Sakdiah (STKIP Subang, 2024)
This research aims to develop Flipbook-based E-Module teaching materials so that they are suitable for use as varied, creative and innovative learning media on theme 1 sub-theme 2 human growth and development learning 1 in class III SDN Kedung Umpal 01. Development of E-Module teaching materials Flipbook-based makes students more interested and active in the learning process in the classroom. This research was conducted using the Research and Development (R&D) method with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model. To determine the feasibility test, a validation sheet is used by a material expert with results obtained in the feasible category. The research results from validation of media, language and material aspects show that the Flipbook E-Module is very suitable for use with an average percentage of 90%. Meanwhile, the results of research on student responses show that the Flipbook E-Module is very suitable for use with a gain of 100%. Based on the research results, it shows that the E-Module based on the Flipbook application can be categorized as very feasible, effective and practical for students to use in learning.